Poverty Reduction in Perspective Economic Islamic - Adzil Arsyi Sabana; Desti Wulandari (International Journal of Management Progress, 2023)
The purpose of this study was to determine the pattern of implementation of the poverty alleviation program, the role of the poverty alleviation program and the poverty alleviation pattern of the people of Ponre Waru Village, Wolo District, Kolaka Regency in an Islamic economic perspective. The results and conclusions from this study are that the implementation pattern of the community poverty alleviation program in Ponre Waru Village, Wolo District, Kolaka Regency is in accordance with the guidelines and provisions of the implementation of PKH and BLT and is on target according to the criteria for beneficiaries, the effect of the community poverty alleviation program in Ponre Waru Village with the PKH and BLT programs really helped the village community, because with this assistance it really helped the poor and vulnerable people in Ponre Waru Village and were able to meet the community's primary needs, namely daily needs and secondary needs, namely education and health as well as village development as an assistance program that can indirectly help the people in the village. According to an Islamic economic view, there are 4 patterns of poverty alleviation with Islamic economic principles, namely the principle of monotheism, the principle of balance, the principle of caliph and the principle of justice. In the Islamic economic principles in the implementation of PKH and BLT in Ponre Waru Village it has been applied. Even though the principle of justice has not been fully implemented because there are still people in the village who often complain about determining the prospective beneficiaries and these people can be said to still be in the poor category.